Reaching the Elderly: Understanding of health and preventive experiences for a tailored approach – Results of a qualitative study. Issue 1 (December 2016) - Patzelt, Christiane; Heim, Susanne; Deitermann, Bernhilde; Theile, Gudrun; Krauth, Christian; Hummers-Pradier, Eva; Walter, Ulla
Abstract Background Often preventive measures are not accessed by the people who were intended to be reached. Programs for older adults may target men and women, older adults, advanced old age groups and/or chronically ill patients with specific indications. The defined target groups rarely participate in the conception of programs or in the design of information materials, although this would increase accessibility and participation. In the German "Reaching the Elderly" study (2008–2011), an approach to motivating older adults to participate in a preventive home visit (PHV) program was modified with the participatory involvement of the target groups. The study examines how older men and women would prefer to be addressed for health and prevention programs. Methods Four focus groups (N  = 42 participants) and 12 personal interviews were conducted (women and men in 2 age groups: 65–75 years and ≥ 76 years). Participants from two districts of a major German city were selected from a stratified random sample (N  = 200) based on routine data from a local health insurance fund. The study focused on the participants' knowledge about health and disease prevention and how they preferred to be approached and addressed. Videos of the focus groups were recorded and analysed using mind mapping techniques. Interviews were digitally recorded, transcribed verbatim and subjected to qualitative content analysis. Results A gender-specific approach profile was observed. Men were more likely to favor competitive and exercise-oriented activities, and they associated healthy aging with mobility and physical activity. Women, on the other hand, displayed a broader understanding of healthy aging, which included physical activity as only one aspect as well as a healthy diet, relaxation/wellness, memory training and independent living; they preferred holistic and socially oriented services that were not performance-oriented. The "older seniors" (76+) were ambivalent towards certain wordings referring to aging. Conclusions Our results suggest that gender-specific needs must be considered in order to motivate older adults to participate in preventive services. Age-specific characteristics seem to be less relevant. It is more important to pay attention to factors that vary according to the individual state of health and life situation of the potential participants.